2006
DOI: 10.1007/s00428-006-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of invasion and histological growth as prognostic indicators in urothelial carcinoma of the upper urinary tract

Abstract: The biological significance of squamous and glandular differentiation and different patterns of invasion in upper urinary tract urothelial carcinoma is unclear. We reviewed 268 cases of consecutive upper urinary tract carcinomas with respect to the presence of squamous and/or glandular differentiation and different patterns of invasion (nodular, trabecular, and infiltrative) and correlated data with patient outcome. Squamous or glandular differentiation occurred in 47/268 (18%) tumors and its presence correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 41 publications
3
20
0
5
Order By: Relevance
“…18,27 Recently, Langner and colleagues have demonstrated that the infiltrative pattern was significantly associated with the development of metastatic disease and proved to be an independent prognostic marker of survival after RNU. 11 Approximately 28% of patients in our series demonstrated sessile tumor growth pattern, and this feature was independently associated with risk of tumor recurrence and cancer-specific survival, further affirming that tumor architecture is a reliable prognostic factor for patients with UTUC. We found that, at 5 years after RNU, 21% of patients with papillary growth pattern recurred and 18% died of UTUC, compared with 60% and 54% of patients whose tumors were sessile.…”
Section: 46supporting
confidence: 72%
See 1 more Smart Citation
“…18,27 Recently, Langner and colleagues have demonstrated that the infiltrative pattern was significantly associated with the development of metastatic disease and proved to be an independent prognostic marker of survival after RNU. 11 Approximately 28% of patients in our series demonstrated sessile tumor growth pattern, and this feature was independently associated with risk of tumor recurrence and cancer-specific survival, further affirming that tumor architecture is a reliable prognostic factor for patients with UTUC. We found that, at 5 years after RNU, 21% of patients with papillary growth pattern recurred and 18% died of UTUC, compared with 60% and 54% of patients whose tumors were sessile.…”
Section: 46supporting
confidence: 72%
“…Whereas tumor stage and histologic grade are well established prognostic factors of outcome after RNU, the oncologic significance of other potentially relevant variables, such as tumor site, architecture, histologic tumor necrosis, lymphovascular invasion (LVI), and the presence of concomitant carcinoma-in situ (CIS), among others, has not been clearly established. 4,[8][9][10][11][12][13][14][15] Recognizing these limitations, we developed a comprehensive database incorporating the clinical and pathologic characteristics and outcomes of over 1300 patients treated with RNU for UTUC at 12 academic centers. Using this large international patient cohort, strict accrual criteria, and pathologic re-review of all slides, we sought to more clearly define the natural history, patterns of failure, and the impact of potential prognostic factors on relapse and survival after surgical management of UTUC.…”
mentioning
confidence: 99%
“…128 The significance of assessing tumor growth pattern has been highlighted in a recent study. 129 The 5-year metastasis-free survival rates for urothelial carcinoma with nodular, trabecular, and infiltrative invasion pattern were 94, 74, and 12%, respectively. 129 …”
Section: Tumor Growth Patternmentioning
confidence: 95%
“…129 The 5-year metastasis-free survival rates for urothelial carcinoma with nodular, trabecular, and infiltrative invasion pattern were 94, 74, and 12%, respectively. 129 …”
Section: Tumor Growth Patternmentioning
confidence: 95%
“…Pet godina nakon radikalne nefroureterektomije 40% pacijenta sa papilarnim karcinomom i 70% onih sa sesilnim je imalo recidiv [63]. Sesilni tip tumora je značajno više povezan sa nastankom metastatske bolesti i predstavlja nezavisni prediktor kancer specifičnog preživljavanja [64]. Preoperativni prognostički model koji kombinuje ovaj parametar sa histološkim gradusom i lokacijom tumora može sa tačnošću od 76,6% da predvidi ishod tumora gornjeg urotelijuma [42].…”
Section: -3 Prognostički Faktori Za Tumore Gornjeg Urotelijumaunclassified